If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1b = m(x + -1a) * fora Reorder the terms: -1b + y = m(x + -1a) * fora Reorder the terms: -1b + y = m(-1a + x) * fora Reorder the terms for easier multiplication: -1b + y = m * afor(-1a + x) Multiply m * afor -1b + y = afmor(-1a + x) -1b + y = (-1a * afmor + x * afmor) Reorder the terms: -1b + y = (afmorx + -1a2fmor) -1b + y = (afmorx + -1a2fmor) Solving -1b + y = afmorx + -1a2fmor Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1y' to each side of the equation. -1b + y + -1y = afmorx + -1a2fmor + -1y Combine like terms: y + -1y = 0 -1b + 0 = afmorx + -1a2fmor + -1y -1b = afmorx + -1a2fmor + -1y Divide each side by '-1'. b = -1afmorx + a2fmor + y Simplifying b = -1afmorx + a2fmor + y
| (x^2+2x-12)=0 | | 36=5x^2-11 | | 5y+3x+10=180 | | 5x^2-8x+4=10 | | 4x+12+4=0 | | -12-28z+5z^2= | | k+(1/5)=3(k/2) | | 4x^3+5x^2-7x-5=0 | | 6=(t^2-t)/2 | | 3r5/9 | | x^3+15x^2+68x+84=0 | | x(x^2+2x-12)=0 | | x^3+15x^2+68x=84 | | x^3-2x^2-2x-8=0 | | t(t^2-12)=-6 | | x+0.03x=3345.44 | | 4+3(3x-1)=9 | | x^3-12x+6=0 | | 5/60=x/40 | | 7-8m=2 | | 3x^2-4x=8-2x | | t^3+-12t+6=0 | | 5x-25=x+30 | | (3x+12)(x+4)=0 | | m(x)=(3x-1)(3-x)+4x^2+9 | | f(x)=x^2-9x-9 | | 6x-21=9x+6 | | 3b-6-8b-3= | | 4(m-8)-31+5m= | | 18k^2+21k-30= | | 59p+60=8p | | 36=x(5x-11) |